1985
DOI: 10.1002/srin.198500631
|View full text |Cite
|
Sign up to set email alerts
|

Stress and deformation analysis of plane‐strain rolling process

Abstract: A finite‐element elastic‐plastic deformation analysis is required in order to predict a complete stress and deformation in a material for metal forming. There have been a few attempts for rolling analysis using the elastic‐plastic code, because the boundary conditions between roll and deforming material become complicated. In this study, an elastic‐plastic plane‐strain rolling analysis with friction has been attempted by the updated Lagrange code. Both slipping and sticking were taken into account for boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The formation of a transition region is the result of reduced shear strain because there is a shear stress gradient with the shear stress being the highest at the surface. [7,30,31] This is discussed more in the next section. The fine grains in the outermost region are slightly elongated in the rolling direction as shown in Figure 1(b).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The formation of a transition region is the result of reduced shear strain because there is a shear stress gradient with the shear stress being the highest at the surface. [7,30,31] This is discussed more in the next section. The fine grains in the outermost region are slightly elongated in the rolling direction as shown in Figure 1(b).…”
Section: Resultsmentioning
confidence: 97%
“…[7,31] It is evident that microbands, which consist of long, thin grains, are formed within the near-surface region by hot-and cold-rolling processes. During increased temperature deformation, the formation of long, thin grains is favored by the reduced rate of formation of high-angle boundaries.…”
Section: A Formation Of the Near-surface Deformed Layermentioning
confidence: 99%
“…Hwu and Lenard (1988) have used a finite element formulation for flat rolling process to assess the effects of work-roll deformation and various friction conditions on the strain field. Yarita et al (1988) have analyzed the plane strain rolling process utilizing an elastic-plastic finite element model. They have attempted to predict the stress and strain distribution within the deformation zone using an updated Lagrangian code.…”
Section: Introductionmentioning
confidence: 99%
“…A high level of plastic strain is introduced into the surface/near-surface region of the work-piece by mutual sliding contact during rolling [1,4]. Yarita et al [7] suggested that the shear strain in the roll bite is highest on the surface and decreases gradually from the surface to the centre of the bulk material. Further, the shear strain undergoes a reversal in the neutral plane of roll bite.…”
Section: Resultsmentioning
confidence: 99%